<h2>
Answer:</h2>
x = 1
y = 1
<h3>
Step-by-step explanation:</h3>
![y=-3x+4\\ y=x](https://tex.z-dn.net/?f=y%3D-3x%2B4%5C%5C%20y%3Dx)
Substitute into one of the equations
![-3x+4=x](https://tex.z-dn.net/?f=-3x%2B4%3Dx)
Rearrange variables to the left sider of the equation
![-3x-x=-4](https://tex.z-dn.net/?f=-3x-x%3D-4)
Combine like terms
![-4x=-4](https://tex.z-dn.net/?f=-4x%3D-4)
Divide both sides of the equation by the coefficient of variable
![x=\frac{-4}{-4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-4%7D%7B-4%7D)
Determine the sign for multiplication or division
![x=\frac{4}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B4%7D%7B4%7D)
Cross out the common factor
![x=1](https://tex.z-dn.net/?f=x%3D1)
Substitute into one of the equations
![y=1](https://tex.z-dn.net/?f=y%3D1)
The solution of the system is
![\left \{ {{x=1} \atop {y=1}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bx%3D1%7D%20%5Catop%20%7By%3D1%7D%7D%20%5Cright.)
<em>I hope this helps you</em>
<em>:)</em>
A) 6(4)^1-6(4)^0 = 24-6 = 18
6(4)^3-6(4)^2 = 384-96 = 288
b) It is 27.11 times difference. This is because g(x) is an exponential function and so as x increases, g(x) increases faster.
C. The answer is C because the total amount of students is 14, and there are 4 boys, which makes the ratio 4 boys to 14 students in total. 4 and 14 are both divisable by 2, so divide 4 to get 2 and divide 14 to get 7. This leaves you with 2 and 7. The ratio would be 2 boys to 7 total students. Hope this helped
Answer:
Step-by-step explanation:
Answer:
G =3
Step-by-step explanation:
if you multiply out x+7 and x-4 you get x^2+3x-28
The 3 in the above equation is like the G